Allelopathic activity of Phragmites australis against Bolboschoenus planiculmis and the involved active allelochemicals - Yang, Liu; Chen, Chong; Wang, Yong; Wang, Jingyao; Shi, Fengxue; Yue, Keming; Wang, Xue; He, Chunguang (Frontiers in Plant Science, 2025)
IntroductionBolboschoenus planiculmis (F. Schmidt) T. V. Egorova plays an important ecological role in wetland ecosystems by providing essential habitat and food resources for the critically endangered Siberian crane (Grus leucogeranus). It frequently coexists with Phragmites australis (Cav.) Trin. ex Steud. (reed) in natural wetland communities; however, the allelopathic activity of reed on B. planiculmis remains poorly understood.MethodsThis study investigated the allelopathic effects of reed on B. planiculmis and identified the phenolic allelochemicals involved. Aqueous extracts from individual reed organs (roots, stems, and leaves), as well as from a mixture of these organs in equal mass proportions, were prepared at two concentrations (7% and 14%) using plant materials collected during both the nutrient and reproductive growth stages.Results and discussionPot experiments revealed that reed aqueous extracts exhibited significant inhibitory activity on the germination and seedling growth of B. planiculmis. The leaf extract showed relatively stronger inhibitory effects compared to the extracts of other organs, especially in the nutrient growth stage. A total of 24 phenolic compounds, including 13 phenolic acids, 9 flavonoids, and 2 coumarins, were identified as potential allelochemicals in reed aqueous extracts. The concentration of phenolic allelochemicals in leaf extract was much higher than that in root and stem extracts. These findings demonstrate the allelopathic inhibitory effect of reed on the germination and seedling growth of B. planiculmis, primarily mediated by active phenolic compounds derived from leaves. Notably, this study is the first to identify flavonoids and coumarins, in addition to phenolic acids, as potential allelochemicals contributing to the allelopathic effects of reed on B. planiculmis in wetland ecosystems. This study enhances our understanding of ecological interactions among wetland plants and provides guidance for the conservation and management of the key functional species B. planiculmis.